Recent developments in microfluidic chip-based separation devices coupled to MS for bioanalysis. (October 2013) - Lin, Shu-Ling; Lin, Tzuen-Yeuan; Fuh, Ming-Ren
In recent years, the development of microfluidic chip separation devices coupled to MS has dramatically increased for high-throughput bioanalysis. In this review, advances in different types of microfluidic chip separation devices, such as electrophoresis- and LC-based microchips, as well as 2D design of microfluidic chip-based separation devices will be discussed. In addition, the utilization of chip-based separation devices coupled to MS for analyzing peptides/proteins, glycans, drug metabolites and biomarkers for various bioanalytical applications will be evaluated.